‘I feel good here’ - Ellen Parsland; Gabriella Scaramuzzino (Journal of Comparative Social Work)
The aim of this article is to understand how a group of subsidised employees constructed a collective identity and symbolic community, and the role the municipal labour market programme played in that process. Further, it explores whether and how a shared collective identity and symbolic community may provide an explanation for how the ‘successful intervention/lock-in effect paradox’ occurs when using subsidised employment as an activation intervention. The article is based on a qualitative interview study with eight social workers and 11 subsidised employees from a Swedish municipal labour market programme that offered subsidised employment as its main intervention. The interviews were analysed using the concepts of social identity and symbolic community. The article shows that subsidised employment plays a crucial role in subsidised employees constructing their identity as ‘persons with a job’, as distinct from the activation interventions usually associated with social assistance. The labour market programme serves as a transformative space where receiving a salary becomes a symbol of distinction, marking a significant departure from past experiences of receiving social assistance. The article also highlights the role of social workers in subsidised employees’ identity processes. The social workers perceived the subsidised employees as participants with special needs, and subsidised employment as an intervention which could influence the planning and support provided during the subsidised employment. The collective identity developed by the participants fostered a sense of community, but also led to reluctance to leave the programme, driven by the fear of reverting to social assistance, and once again being excluded from the labour market. The article concludes that the subsidised employees risked getting stuck in a borderland between work exclusion and work inclusion and, therefore, that subsidised employment can potentially place participants in a state of ‘marginalised inclusion’ in the labour market, instead of supporting participants into regular employment.